2016
DOI: 10.5301/jbm.5000201
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Cancer Susceptibility Genes XRCC1, RAD51 and TP53 and the Risk of Breast Cancer in Serbian Women

Abstract: The XRCC1 R399Q polymorphism showed an association with increased breast cancer risk in Serbia, especially in the hereditary form of the disease and in young breast cancer patients. Dominant alleles of RAD51, TP53 and XRCC1 combined genotypes indicated a strong protective role against hereditary breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…HR and NHEJ, belonging to DSBR, are involved in the damage repair by competition or cooperation. Not surprisingly, numerous studies have identified polymorphisms located in genes of DSBR associated to the risk of a variety of benign and malignant tumors, for example, XRCC1 R399Q in breast cancer, 18 RAD51 135G/C in colorectal cancer, 19 XPD Lys751Gln in prostate cancer and so on. 20 The present study focuses on the effect of 3ʹ-UTR polymorphisms of DSBR genes on PTC risk based on a medium-sized case–control study.…”
Section: Discussionmentioning
confidence: 99%
“…HR and NHEJ, belonging to DSBR, are involved in the damage repair by competition or cooperation. Not surprisingly, numerous studies have identified polymorphisms located in genes of DSBR associated to the risk of a variety of benign and malignant tumors, for example, XRCC1 R399Q in breast cancer, 18 RAD51 135G/C in colorectal cancer, 19 XPD Lys751Gln in prostate cancer and so on. 20 The present study focuses on the effect of 3ʹ-UTR polymorphisms of DSBR genes on PTC risk based on a medium-sized case–control study.…”
Section: Discussionmentioning
confidence: 99%
“…21 In the study of Ragudo et al (2020) 36 , the more common RAD51 G/C genotype was not associated with breast cancer development among Filipinos, while the less common recessive C/C genotype was observed to potentially increase the risk. XRCC1 Arg399Gln has been associated with breast cancer among Serbian women 22 and lung cancer among Chinese. 23 Both RAD51 135G>C and XRCC1 Arg399Gln have been associated with ovarian cancers among Serbian women.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that there was a relationship between SNPs and BC. Al Zoubi et al 29 found that polymorphisms and mutations in RAD51 and XRCC3 genes increased the risk of BC; Krivokuca et al 30 reported an association between XRCC1 polymorphism and BC; and the results of meta-analysis showed that the MDM4 SNP34091 A>C polymorphism may function as a protective factor against cancer risk. 31 Our study found that rs12922061 of LOC643714 was a risk factor for BC.…”
Section: Discussionmentioning
confidence: 99%